A new crystalline form of αβ‐d‐lactose prepared by oven drying a concentrated aqueous solution of d‐lactose. Issue 7 (14th June 2019) - Nicholls, Daniel; Elleman, Carole; Shankland, Norman; Shankland, Kenneth
Abstract : A monoclinic polymorph of αβ‐d ‐lactose has been identified from crystalline phase mixtures obtained by oven drying concentrated aqueous solutions ofd ‐lactose. This is the second crystalline form of αβ‐d ‐lactose to be identified and it has a high degree of structural three‐dimensional similarity to the previously identified triclinic form. Abstract : A new crystalline form of αβ‐d ‐lactose (C12 H22 O11 ) has been prepared by the rapid drying of an approximately 40% w / v syrup ofd ‐lactose. Initially identified from its novel powder X‐ray diffraction pattern, the monoclinic crystal structure was solved from a microcrystal recovered from the generally polycrystalline mixed‐phase residue obtained at the end of the drying step. This is the second crystalline form of αβ‐d ‐lactose to be identified and it has a high degree of structural three‐dimensional similarity to the previously identified triclinic form.